2017
DOI: 10.1590/abd1806-4841.20175918
|View full text |Cite
|
Sign up to set email alerts
|

Nail psoriasis treated with pulsed dye laser

Abstract: Nail changes are present in about 50% of psoriasis patients and tend to be refractory to conventional treatments. Pulsed dye laser has emerged as an alternative therapy. Our aim is to evaluate the efficacy of pulsed dye laser in nail psoriasis and the impact of treatment on quality of life. Fourteen patients were treated in monthly sessions for three months. The outcome assesment was made by the Nail Psoriasis Severity Index (NAPSI). The median improvement in the scores of the overall NAPSI, nail bed NAPSI, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Although the application parameters of the 595-nm PDL were in part comparable with that of prior studies, [4][5][6][7][8][9] we observed a disparity in effectiveness that could be attributed to fewer sessions or non-use of concomitant therapy in our cohort.…”
supporting
confidence: 79%
“…Although the application parameters of the 595-nm PDL were in part comparable with that of prior studies, [4][5][6][7][8][9] we observed a disparity in effectiveness that could be attributed to fewer sessions or non-use of concomitant therapy in our cohort.…”
supporting
confidence: 79%
“…Nail psoriasis is graded with the Nail Psoriasis Severity Index, otherwise known as NAPSI score. NAPSI scores improved in nail psoriasis treated with PDL monotherapy but no significant difference was found between varying pulse durations of PDL and NAPSI scores, although both durations (6 and 0.45ms, respectively) were found to be efficacious . PDL was found to be more effective in treating nail psoriasis than excimer laser but interestingly less effective in plaque psoriasis .…”
Section: Psoriasismentioning
confidence: 82%
“…PDL was selected as an appropriate treatment option in this case because it has been documented as a practical solution for dystrophic nails associated with psoriasis. 20 , 21 Possible PDL action mechanism in psoriatic nails, including selectively eliminating abnormal vasculature and reducing inflammation by decreasing the T-lymphocyte count on the skin. 21…”
Section: Discussionmentioning
confidence: 99%